Em busca de ser decolonial: rupturas e deslocamentos de uma professora de inglês a partir do Programa Escola em Casa - Martins, Suéllen Flauzina (2024)
The objective of this research is to investigate my role as an English teacher in the production of English video classes in the program called Escola em Casa, under decolonial lenses. I rely on autoethnographic, interpretative, qualitative research to analyze my trajectory, understanding the duality of being the researcher/researched (Pardo, 2019) and also understanding the exposure of my practices (Ono, 2018). From a decolonial perspective, my reflections are based on authors such as Quijano (2005, 2010), Mignolo (2011, 2013), Walsh (2013, 2018), Dussel (2000), Maldonado-Torres (2008), Menezes de Souza (2019, 2022), among many others. I also mention authors who offer critical perspectives for this area, even without explicitly mentioning the concept of decoloniality, such as Freire (2008, 2013), Bispo dos Santos (2015, 2023), Bento (2022), and Pinheiro (2023). This research study involves an analysis of multiple elements. Thirty-six lessons from the Escola em Casa Program were analyzed, in their raw and edited versions, which were designed by me. In addition, reflective journals I wrote during my participation in the Program were considered, as well as interviews with English teachers who participated in the same Program. Data analysis demonstrated the (im)possibilities of a decolonial attitude in English language video lessons. This included not only the general difficulties faced by most education professionals and the general population during the pandemic, but also the specific challenges associated with the Program Escola em Casa. However, it was also possible to identify the initial efforts of a decolonial perspective in the video lessons. Furthermore, the many colonialities that constitute me were identified, including the emphasis on a traditional approach to language teaching, which tends to make marginalized cultures invisible. I also highlight the discovery of whiteness in my own identity, an aspect that was not anticipated in my initial analyses. At the same time, supported by decolonial studies, I analyzed my trajectory as an English language teacher when performing different roles and identified how my perspectives of language and English teaching were transformed, amid conflicts and paradoxes. My trajectory revealed an urgency to adopt a decolonial perspective, especially in the context of public schools, which I see as a space of resistance. However, it also demonstrated the lengthy path to be covered, highlighting the need to understand my own incompleteness in this process.